SAT0474 WHAT DETERMINES THE EFFECT OF THERAPY WITH DENOSUMAB ON BONE IN WOMEN WITH RHEUMATOID ARTHRITIS AND OSTEOPOROSIS. (2nd June 2020) - Kovalenko, P.; Dydykina, I.; Smirnov, A.; Nasonov, E.
Abstract : Background: RANK-ligand is essential for osteoclast development, activation, and survival and it is a key mediator of increased osteoclast activity in rheumatoid arthritis (RA). Denosumab is a monoclonal antibody that binds RANK-ligand. Objectives: The aim of this study was to evaluate the effects of denosumab on bone mineral density (BMD) and to define a contribution of factors: anamnesis, clinical/laboratory markers, glucocorticoids (GC) intake, etc. on the response to therapy with denosumab in women with RA and osteoporosis (OP). Methods: 66 postmenopausal women (mean age 59, 6±7, 4) with RA (mean duration 17, 7±10, 4 years) and OP received s/c denosumab 60 mg every 6 months pro 12 months. RF-positive were 72%, ACCP – 74% of patients. 34 (49%) patients continued GC. At baseline and after 12 months it was carried out the dual energy x-ray absorptiometry at 3 sites: lumbar spine (L1-L4), hip neck (HN) and distal forearm (DF) and x-ray of hands and feet (Sharp/van der Heijde (SVH) score). The Statistica 6.0 was used. Results: After therapy it was noted the increase (р < 0, 05) of BMD in L1-L4 and HN, a tendency to increase (р =0, 0529) in DF. Mean BMD (L1-L4) beforethe treatment was 0, 821 ± 0, 104 g/cm 2 vs 0, 864 ± 0, 110 g/cm 2, at HN was 0, 625 ± 0, 089 g/сm 2 vs 0, 639 ± 0, 088 g/сm 2, at DF was 0, 498 ± 0, 090 g/сm 2 vs 0, 503 ± 0, 089 g/сm 2 . The mean change of BMD (%) after 12 months at L1-L4 was +4, 6%, at HN +2, 8%, at DF +0, 7%. Positive response (increase or stabilization of BMD) was noted in 89% patients at L1-L4, 67% - at HN and 60% - at DF. Analysis of influence of various factors (statistically significant) on the response to therapy is presented in the Table. Conclusion: After 12 months of therapy with denosumab in postmenopausal women with RA and OP it was shown the significant increase of BMD in L1-L4 and HN, a tendency to increase in DF. The mean change of BMD (%) after 12 months was +4, 6% at L1-L4, at HN +2, 8%, at DF +0, 7%. Positive response on denosumab (BMD) was noted in 89% patients at L1-L4, 67% - at HN and 60% - at DF. Analysis of influence of factors on the response to therapy showed that positive response on therapy in NH and DF was associated with RF-positivity. The distinct contribution to the negative response in L1-L4 and HN was associated with GC intake (previous intake more than 3 months in the anamnesis) and purpose of the GC after menopause onset. Also, negative response in DF back correlated with increase in erosion score and total SVH score. Disclosure of Interests: None declared